Humildade intelectual: uma introdução crítica ao debate filosófico contemporâneo - BOTTI, Ian Salles (2024)
Intellectual humility is a character trait that has drawn the interest of researchers from various fields, but the variety of definitions proposed in recent decades attests to the difficulty of answering the fundamental question that concerns philosophers: what is it? The objective of this dissertation is to provide a critical introduction to the contemporary philosophical debate on intellectual humility. Given the lack of consensus on its conceptual analysis, we approach intellectual humility without the intention of resolving the debate or determining which theory is the best. Instead, we conduct a critical examination of the main theories, aiming to represent it in a pluralistic way, highlighting its fundamental characteristics from different perspectives. To organize the types of theories and better understand the disagreement among philosophers, we propose the division between internalist and externalist theories. The former defines humility in terms of internal dispositions of the agent, while the latter defines it in terms of elements external to the agent and their relationships with others. Internalist theories can be cognitivist or non-cognitivist, while externalist theories can be interpersonal or existential. Based on this categorization, we present in detail internalist conceptions of intellectual humility, aiming to offer a partial representative framework of the state of the art in philosophical research on this intellectual virtue.